TOWARDS AGILE GOVERNMENT: WHAT THINGS DOES THE GOVERNMENT NEED TO BE READY? - Malik, Kurniawan Jabar; Sumaryadi, Adityo; Kusudiandaru, Sandhi (DIA: Jurnal Administrasi Publik, 2024)
In recent years, there has been a relatively rapid, dynamic world situation, and it has influenced various sectors. These changes include the massive changes in information technology, patterns of people's lives after the COVID-19 pandemic, demographic shifts, and the evolution of generations of society. The private sector and start-ups often apply the issue of agility and use a strong foundation for implementing digital technology. However, the good things about agile principles are also seen as driving change in the government sector. This research uses literature study and comparative study methods to see how the agile government concept can be built based on structure, culture, operations, and capabilities. The results of this research show that preparing an agile government will be related to how to manage the agility so that the government focuses on user needs, builds the prime team in a dynamic environment, and has the specific role of product owner-product manager as well as the existence of a clear time frame for completing a strategic/priority project.